Bullying's Impact on Mental Health of Islamic Boarding School Students in Dormitories - Karmila, Lisa Puspa; Martha, Evi (Indonesian Journal of Global Health Research, 2024)
Islamic boarding schools as religious-based educational institutions have an important role in shaping the character and personality of students. However, increasingly intensive interactions in the dormitory environment and social pressure between students often create conditions that are vulnerable to bullying behavior, both verbal and physical. This study highlights the impact of bullying on the mental health of students in the Islamic boarding school environment, where intimidation behavior can trigger anxiety disorders, depression, and decreased self-esteem. Methods The study used a systematic review method using PRISMA (Preferred Reporting Items for Systematic Review and Meta-Analysis). database search by searching for articles from 3 databases, namely Google Scholar, Science Direct and Scopus. Obtained 162 articles with the keywords "Impact of Bullying", "Mental Health", and "Boarding School". Bullying victims experience various psychological disorders, such as trauma, stress, fear, and the desire to leave the Islamic boarding school. Bullying also has a direct effect on increasing depression, anxiety, and decreased self-esteem of victims. In addition, negative emotions such as anger and the urge to take revenge can cause victims to become perpetrators, creating a continuous cycle of revenge. Bullying victims often show signs of anxiety, loss of enthusiasm for learning, and difficulty rebuilding a sense of security in their social environment.Bullying in the Islamic boarding school environment has a significant impact on the mental health of students, including trauma, anxiety, stress, and decreased self-esteem. In addition, some victims show defensive behavior that develops into aggression, creating a cycle of revenge. The long-term effects of bullying not only affect psychological well-being, but also disrupt the social and academic lives of victims. Therefore, a comprehensive approach is needed in the form of emotional support, protection, and effective policies to minimize the negative impacts of bullying in the Islamic boarding school environment.